2012
DOI: 10.1016/j.bbi.2012.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Maternal immune activation by LPS selectively alters specific gene expression profiles of interneuron migration and oxidative stress in the fetus without triggering a fetal immune response

Abstract: Maternal immune activation (MIA) is a risk factor for the development of schizophrenia and autism. Infections during pregnancy activate the mother’s immune system and alter the fetal environment, with consequential effects on CNS function and behavior in the offspring, but the cellular and molecular links between infection-induced altered fetal development and risk for neuropsychiatric disorders are unknown. We investigated the immunological, molecular, and behavioral effects of MIA in the offspring of pregnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
149
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 215 publications
(168 citation statements)
references
References 114 publications
12
149
1
1
Order By: Relevance
“…This is consistent with findings that placental size correlates with the risk for several adultonset diseases [49][50][51][52]. Acute transcriptional changes and cytokine effects in the fetal brain may serve as an underlying basis for several of the neurodevelopmental impairments observed in MIA offspring (reviewed in [15][16][17][18] [16]. At the same time, the information garnered from diverse MIA studies raises the intriguing question of whether differences in the severity, timing and type of MIA can produce distinct forms of neurodevelopmental disorders.…”
Section: Immune-related Risk Factors For Asdsupporting
confidence: 77%
See 2 more Smart Citations
“…This is consistent with findings that placental size correlates with the risk for several adultonset diseases [49][50][51][52]. Acute transcriptional changes and cytokine effects in the fetal brain may serve as an underlying basis for several of the neurodevelopmental impairments observed in MIA offspring (reviewed in [15][16][17][18] [16]. At the same time, the information garnered from diverse MIA studies raises the intriguing question of whether differences in the severity, timing and type of MIA can produce distinct forms of neurodevelopmental disorders.…”
Section: Immune-related Risk Factors For Asdsupporting
confidence: 77%
“…Consistent with this notion, poly (I:C) offspring exhibit dynamic age-and regionspecific changes in brain cytokines throughout postnatal development [45,46]. In response to maternal LPS, fetal brains exhibit altered gene expression profiles, with upregulation of genes related to oxidative stress and down regulation of genes related to GABAergic interneuron migration [15]. After maternal influenza infection, embryos exhibit altered brain expression of many genes relevant to autism and schizophrenia, including Sema3a, Foxp2 and Vldlr [47].…”
Section: Immune-related Risk Factors For Asdmentioning
confidence: 59%
See 1 more Smart Citation
“…Prenatal LPS may affect both mechanisms. Indeed, a decreased expression of transcription factors regulating neuronal migration was observed 4 h after LPS injection to pregnant dams, supporting the hypothesis of a migration disorder (28). On the other hand, prenatal immune challenge may also alter neurogenesis in the fetal and young offspring's brain (29).…”
Section: Discussionsupporting
confidence: 52%
“…In the present study, we found an early (P10) deficit in reelin-expressing neurons after prenatal LPS, most prominent in the CA3 area. This deficit was transient and might support the hypothesis of migration disorders (28). There is a general consensus for a progressive decrease of the number of reelin-producing cells during postnatal development (34,35).…”
Section: Prenatal Lps Effects On Reelin Neuronssupporting
confidence: 53%